Monitoring Vadose Zone Desiccation with Geophysical Methods. Issue 2 (2nd May 2013) - Truex, M.J.; Johnson, T.C.; Strickland, C.E.; Peterson, J.E.; Hubbard, S.S.
Abstract : Soil desiccation was recently field tested as a potential vadose zone remediation technology. Desiccation removes water from the vadose zone and significantly decreases the aqueous‐phase permeability of the desiccated zone, thereby decreasing movement of moisture and contaminants. The two‐ and three‐dimensional distribution of moisture content reduction with time provides valuable information for desiccation operations and for determining when treatment goals have been reached. This type of information can be obtained through the use of geophysical methods. Neutron moisture logging, cross‐hole electrical resistivity tomography, and cross‐hole ground‐penetrating radar approaches were evaluated with respect to their ability to provide effective spatial and temporal monitoring of desiccation during a treatability study conducted in the vadose zone of the USDOE Hanford site in the state of Washington.